Hubungan Status Gizi Dengan Kejadian Diare Pada Balita Di Puskesmas Martapura 1 Kabupaten Banjar - Khofifah, Noor; yuniarti, yuniarti; rizani, Ahmad (Politeknik Kementerian Kesehatan Banjarmasin, 2023)
Diarrhea is a major cause of mortality and morbidity among children less than 5 years of age. Based on data from the Banjar District Health Office in 2019, the Martapura 1 Health Center was the first of 24 health centers in Banjar Regency with the highest number of diarrhea sufferers in toddlers, namely 52.4% of diarrhea cases in toddlers. The purpose of this study was to determine the relationship between nutritional status and the incidence of diarrhea in children under five at the Martapura 1 Health Center. This research method uses an analytical survey with a cross sectional approach. The population of 892 toddlers brought by their parents was taken for treatment to the Martapura 1 Public Health Center aged 1-59 months. The sample taken is 892 respondents. Sampling with the Probability Sampling technique with the Total Sampling Technique. The collection of research data is secondary data. Data analysis using univariate and bivariate analysis techniques using the Sperman Rank test. The results showed that the value of (0.002) < (0.05) thus concluded that there was a significant relationship between nutritional status and the incidence of diarrhea in children under five in the working area of Maartapura 1 Public Health Center, Banjar Regency.